Migrating Strategies, Peasant Identities’ Reformulation, and Participation in Written Culture - Cragnolino, Elisa Rita (Íkala, Revista de Lenguaje y Cultura, 2019)
In this paper, I review analyses resulting from empirical works referred to written practices in rural areas in Córdoba (Argentina). In this case, I will focus on migra-tory strategies deployed by peasant families from the northern part of the province, aiming to reflect upon their incidence in adopting reading and writing practices. I will analyze the role these migratory strategies had on family social reproduction throughout several decades of the 20th century, relating them to structural andpolitical changes, and depeasantization processes. Then I will delve into pro-cesses of identity building-rebuilding within these families. This allows me to bring to discussion some views often encountered in school settings, presenting peasant identities and cultural practices as static, ahistorical and incapacitating re-garding access to education and written culture. To carry out this analysis I found revealing insights in the New Literacy Studies and Pierre Bourdieu’s sociologi-cal approach, since they both helped me to understand how written practices are socially constructed, historically situated, unequally distributed, and occurring within the framework of other practices and social relationships that give them meaning. In both approaches, the key is to consider reading and writing not as independent isolated variables, but as a social practice and a part of a web of relations reconfiguring themselves across local spaces and throughout time.